Foreign body-type giant cell reaction with extensive granulation tissue and intense inflammation after chemotherapy mimicking residual lymphoma on FDG PET - Kazi, Sakib; Raptis, Stavros; Abbaspour, Farzad; Zeng, Wanzhen (Université d'Ottawa | University of Ottawa, 2022)
Abstract Foreign body-type giant cell reaction is typically a biological and immunological reaction to the presence of foreign bodies such as catheters, parasites or biomaterials with a collection of fused macrophages (giant cell). We reported an unusual case of [18F]FDG PET findings in diffuse large B cell lymphoma in the urinary bladder following incomplete resection and chemotherapy. As the restaging [18F]FDG PET showed intense [18F]FDG uptake in the urinary bladder at the resection site concerning for recurrence, the lesion was subsequently resected and histopathology showed extensive granulation tissue with foreign body-type giant cell reaction with no suspected foreign bodies or neoplasia.